The Role of Urban Forest in Providing Landscape Services: A Case Study from Bekasi City, West Java, Indonesia - Fredisa, Yoga; Karlinasari, Lina; Kaswanto, Regan L.; Siregar, Iskandar Z. (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Urban forests are critical green infrastructures that provide multiple landscape services, including carbon sequestration, microclimate regulation, and biodiversity support, thereby contibuting to global climate adaption and urban sustainability. This study aimed to analyze the Patriot Bina Bangsa (PBB) Urban Forest’s role in providing comfort through carbon storage and sequestration using the i-Tree Eco model, microclimate monitoring, and evaluating its contribution to landscape services. Data were collected from 12 sample plots using a stand inventory that refers to the i-Tree Eco data collection protocol. An estimated 750 trees, dominated by Nauclea orientalis and Swietenia macrophylla, with a moderate species diversity index (H' = 1.7). The urban forest stored 241 tons of carbon and sequestered 17.85 tons annually, valued at approximately 151 million rupiah. Temperature Humidity Index (THI) values indicate moderate thermal comfort, especially during peak hours. A multifunctional landscape service assessment shows high for regulation functions and landscape disservices, and medium for habitat, information, and production. These findings highlight the importance of urban forests and tree diversity in maintaining landscape services. The indicators outlined in this study provide a basic method for assessing the services provided by urban forest landscapes. It can be used as a tool to improve the management of urban forest systems and monitor the impact of urban greening policies on human well-being in urban landscapes